Influence of Social and Institutional Factors on Life Insurance Purchase Decisions: Mediating Role of Agent Influence - Thapa, Bhim Kumar; Paudel, Ramesh Rasik (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study aims to examine the influence of cultural perception (CP), peer influence (PI), and trust in institutions (TII) on agent influence (AI) and life insurance policy purchase decisions (PPD) among Nepalese consumers. Additionally, it investigates the mediating role of AI in translating these social and institutional factors into actual PPD.Design/Methodology/Approach: An explanatory research design with a quantitative approach was employed. Cross-sectional data were collected from 385 life insurance policyholders purposively. Data analysis was conducted using SmartPLS 4.0.Findings: The study revealed that AI significantly mediates the effects of CP, PI, and TII on PPD, with CP, PI, and TII exerting no direct impact but influencing PPD indirectly through AI.Conclusion: The study validates a relational model of life insurance decision-making in which AI serves not merely as an intermediary but as a behavioral bridge that connects cultural, social, and institutional antecedents to policy adoption outcomes. Implications: Practically, insurers should strengthen agent capacity, cultural alignment, and institutional credibility to improve uptake. The study contributes a socio-cognitive lens to understanding insurance adoption in emerging markets.Originality/value: This study uniquely integrates social, cultural, and institutional perspectives to explore life insurance purchase behavior in Nepal, a context that remains under-researched in insurance literature.JEL Classification: G22, D91, O17, Z13, C38